2016
DOI: 10.1037/aap0000036
|View full text |Cite
|
Sign up to set email alerts
|

A narrative-linguistic approach to understanding Asian American adolescents’ discrimination experiences.

Abstract: Within the discrimination literature, relatively little qualitative work has focused exclusively on adolescents from Asian American backgrounds. In the present study, 69 adolescents (62% female) wrote short narratives to describe an encounter with ethnic discrimination. Using qualitative content analysis, responses were systematically categorized to gain insight into the types of discrimination experiences faced by Asian American youth. In addition, linguistic characteristics of the narratives were analyzed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The majority of these studies examined the predictors and psychological consequences of perceived racial/ethnic discrimination. A few studies investigated model minority stereotypes and microaggressions (e.g., Kiang et al, 2016; Nadal et al, 2015). One article investigated Asian American adolescents’ discrimination experiences using a narrative-linguistic approach (Kiang & Bhattacharjee, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these studies examined the predictors and psychological consequences of perceived racial/ethnic discrimination. A few studies investigated model minority stereotypes and microaggressions (e.g., Kiang et al, 2016; Nadal et al, 2015). One article investigated Asian American adolescents’ discrimination experiences using a narrative-linguistic approach (Kiang & Bhattacharjee, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Discrimination, including derogatory insults and harassment based on race (see Kiang & Bhattacharjee, 2016), may be an additional risk factor for youth of Asian descent. Despite the model minority myth, a study in the United States found that Asian American youth were more likely than Black and Hispanic American youth to be targets of racial/ethnic discrimination (Cooc & Gee, 2014).…”
Section: Savry With Youth Of Asian Descentmentioning
confidence: 99%
“…Similarly, parental reluctance to allow their child to acculturate into the larger Western society could inhibit youths' ability to develop a positive self-identity, thereby increasing their risk of criminality (Besla et al, 2005). Discrimination, including derogatory insults and harassment based on race (see Kiang & Bhattacharjee, 2016), may be an additional risk factor for youth of Asian descent. Despite the model minority myth, a study in the United States found that Asian American youth were more likely than Black and Hispanic American youth to be targets of racial/ethnic discrimination (Cooc & Gee, 2014).…”
Section: Savry With Youth Of Asian Descentmentioning
confidence: 99%
“…Beyond its academic consequences, the “Model Minority Stereotype” can also impact the relationships that teachers form with Asian American students. Prior work finds that teachers are more likely to form weaker relationships with second-generation Asian Americans (Cherng, 2016), which likely is a reason why Asian American youth and parents also feel invisible from their teachers (Kiang & Bhattacharjee, 2016; Way & Chen, 2000).…”
Section: Discussionmentioning
confidence: 99%